1993
DOI: 10.1002/jrs.1250241213
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational spectra and structure of perchlorinated metal‐free phthalocyanine and lutetium bisphthalocyanine

Abstract: The infrared and Raman spectra of perchlorinated phthalocyanine (Pc), H2PcCI,, , LuPc,CI,, and the unsymmetrical LuPc,CI,, are reported. The vibrational data set also include SERRS and the far-infrared spectra between 100 and 400 cm-'. The vibrational assignment of characteristic wavenumbers was supported by a semiempirical calculation using the PM3 Hamiltonian. The H,Pc molecule was used as a reference in the PM3 vibrational calculations. The effect of the chlorine substituents on the optical spectra of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
2
4
0
Order By: Relevance
“…38 A similar profile is also observed comparing the spectra in Figures 4(a) and (c), i.e., the FTIR spectra for LS and LB films in transmission mode, indicating that both LS and LB present the LuPc 2 Cl 32 structured in a similar way. Besides, all spectra are similar to that observed to LuPc 2 Cl 32 in KBr pellet given by Gobernado-Mitre et al 36 Therefore, because the FTIR spectrum of the powder is characteristic of randomly structured system, it can be concluded that, despite LB and LS grow in a well stratified and packed layers, they present a non-preferential molecular arrangement.…”
Section: Lb and Ls Films-molecular Arrangementsupporting
confidence: 84%
See 1 more Smart Citation
“…38 A similar profile is also observed comparing the spectra in Figures 4(a) and (c), i.e., the FTIR spectra for LS and LB films in transmission mode, indicating that both LS and LB present the LuPc 2 Cl 32 structured in a similar way. Besides, all spectra are similar to that observed to LuPc 2 Cl 32 in KBr pellet given by Gobernado-Mitre et al 36 Therefore, because the FTIR spectrum of the powder is characteristic of randomly structured system, it can be concluded that, despite LB and LS grow in a well stratified and packed layers, they present a non-preferential molecular arrangement.…”
Section: Lb and Ls Films-molecular Arrangementsupporting
confidence: 84%
“…Table I shows a list of vibrational modes and their assignment for LB and LS films. 36 An important point to be noticed here is that according to the surface selection rules 37 the fundamental vibrations with dynamic dipole parallel to the substrate surface have maximum intensity for the FTIR spectra obtained in transmission mode (incident electric field parallel to the substrate surface). In reflection mode (incident electric field polarized perpendicularly to the substrate surface), the intensities of the fundamental vibrations with dynamic dipole perpendicular to the substrate surface have maximum intensity.…”
Section: Lb and Ls Films-molecular Arrangementmentioning
confidence: 93%
“…Macrocycle deformation and isoindole ring deformations exhibit Raman shift in the range of 200–500 cm –1 . Peaks appearing in the frequency ranges of 500–1000 cm –1 correspond to benzene ring deformation and the macrocycle breathing (expansion and contraction) , of MnPc molecules. Regions from 1100 to 1300 arise because of the C–H bending and pyrrole ring stretching.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Raman spectra of 50 nm thick MnPc and I-MnPc films on silicon substrate obtained with 532 nm laser (a) spectra in the region 100-1700 cm -1 , (b) and (c) show the expanded regions of interest for I-MnPc film.10Macrocycle deformation and isoindole ring deformations exhibit Raman shift in the range of 200-500 cm -1 . Peaks appearing in the frequency ranges of 500-1000 cm -1 correspond to benzene ring deformation and the macrocycle breathing (expansion and contraction)33,34 of MnPc molecules. Regions from 1100 to arise due to the C-H bending and pyrrole ring stretching.…”
mentioning
confidence: 99%
“…The heat of formation is calculated for these methods by subtracting atomic heats of formation from the binding energy. MNDO has been used widely to calculate heats of formation, molecular geometries, dipole moments, ionization energies, electron affinities, and other properties [11,12]. MNDO gives better results for some classes of molecule, such as some phosphorus compounds.…”
Section: The Computational Methodsmentioning
confidence: 99%